2010
DOI: 10.1016/j.str.2010.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis of 5′ Triphosphate Double-Stranded RNA Recognition by RIG-I C-Terminal Domain

Abstract: SUMMARY RIG-I is a cytosolic sensor of viral RNA that plays crucial roles in the induction of type I interferons. The C-terminal domain (CTD) of RIG-I is responsible for the recognition of viral RNA with 5′ triphosphate (5′ ppp). However, the mechanism of viral RNA recognition by RIG-I is still not fully understood. Here we show that RIG-I CTD binds 5′ ppp dsRNA or ssRNA, as well as blunt-ended dsRNA, and exhibits the highest affinity for 5′ ppp dsRNA. Crystal structures of RIG-I CTD bound to 5′ ppp dsRNA with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
258
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(282 citation statements)
references
References 41 publications
18
258
1
1
Order By: Relevance
“…Although the blunt-ended 5Ј OH dsRNAs that we have used have not induced IFN upon transfection into cells, Lu et al (17) have reported that a 27-bp blunt-ended 5Ј OH dsRNA does induce IFN. More importantly, they have found that mutation of one of the four basic residues that directly interacts with the 5Ј ppp (K861E) abolished the ability of 5Ј ppp dsRNA to induce IFN but had virtually no effect on that of the 27-bp blunt-ended 5Ј OH dsRNA.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Although the blunt-ended 5Ј OH dsRNAs that we have used have not induced IFN upon transfection into cells, Lu et al (17) have reported that a 27-bp blunt-ended 5Ј OH dsRNA does induce IFN. More importantly, they have found that mutation of one of the four basic residues that directly interacts with the 5Ј ppp (K861E) abolished the ability of 5Ј ppp dsRNA to induce IFN but had virtually no effect on that of the 27-bp blunt-ended 5Ј OH dsRNA.…”
Section: Discussionmentioning
confidence: 81%
“…The high resolution structures of the CTD bound to 5Ј ppp dsRNAs have found that the CTD interacts with dsRNA in large part through extensive electrostatic interactions with the 5Ј ppp group, consistent with the significantly higher affinity of the CTD for 5Ј ppp dsRNAs than for 5Ј OH dsRNAs. Despite the highly electrostatic nature of CTD/ 5Ј ppp dsRNA interactions, both its association and dissociation are relatively slow (17,29). The unique slow dissociation kinetics of this interaction (t1 ⁄ 2 ϭ 327 s), as opposed to that of CTD and 5Ј OH dsRNA (t1 ⁄ 2 ϭ 28s), together with the higher affinity of the 5Ј ppp dsRNA presumably help explain why our 5Ј ppp dsRNA strongly induces IFN, whereas our 5Ј OH dsRNA does not (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous structural studies showed that a KWK motif in the CTD of RIG-I mediates physical interaction between RIG-I and dsRNA, although it is unknown whether the interaction is functionally important (26,27,37). Because the KWK motif is conserved in DRH-1 CTD (Fig.…”
Section: The Helicase and Ctd Domains Of Rig-i Were Functional In A Fmentioning
confidence: 98%
“…Thus, it was thought that RIG-I recognizes dsRNA replicative intermediates of negative stranded single-stranded RNA (ssRNA) viruses, while MDA5 responds to long dsRNA replicative intermediates of plus strand ssRNA viruses [84][85][86][87]. Indeed, the struc-npg ture of RIG-I bound to short dsRNA products has recently been solved [88,89]. RIG-I has also recently been implicated in the recognition of DNA viruses by binding short dsRNAs generated by RNA polIII [90].…”
Section: Pattern Recognition Receptorsmentioning
confidence: 99%